APPLICATIONS PAYROLL SMK BINA PUTRA JAKARTA TEACHER USING MICROSOFT VISUAL BASIC 6.0 - Damayanti Damayanti; Susi Wagiyati P, SKom, MMSI (Jurnal Sistem Informasi, 2003)
At current developments in computer technology is increasing, technology is able to provide information so precise and accurate that no doubt. SMK BINA PUTRA eg JAKARTA in teacher salaries to handle manually. So that work on the calculation of teachers' salaries will spend a long completion.  Then the writer tries to make the application on the teacher salary calculation SMK BINA PUTRA JAKARTA using Visual Basic 6.0. The purpose of the calculation of salaries of teachers at SMK BINA PUTRA JAKARTA namely to facilitate and accelerate the process of beginning teacher salary calculation manually become computerized, so that work done more effectively and efficiently.